Managing resource transposition in the face of extreme events: Fieldwork at two public networks in Germany and the US - Olivier Berthod; Michael Grothe-Hammer; Ryan Hagen; Jörg Sydow (Public Administration, 2021)
As administrations increasingly rely on interorganizational networks to organize public service provision, this article inspects the role resourcing plays in the way managers working in networks cope in the face of extreme events. Using comparative analyses of fieldwork in the context of two emergency service networks in two major cities in Germany and the US, we introduce the concept of resource transposition. This concept holds the potential to explain why and how networks might perform well in situations that drain its central participants' resources. We highlight the relevance of four practices: resource (re)production; resource administration through integration; resource administration through centralization; resource support. We derive a set of propositions underlining the usefulness of the concept of resource transposition.
Keywords: 340